2016
DOI: 10.1007/978-1-4939-6481-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Uveal Melanoma: Vaccination Against Cancer

Abstract: Uveal melanoma is the most frequently occurring primary intraocular tumor in adults, with an incidence of about 5 out of 100,000 per year, the incidence rising with increasing age (Lipski, Klin Monbl Augenheilkd 230:1005-1019, 2013; Metz et al., Klin Monbl Augenheilkd 230:686-691, 2013; Singh and Topham, Ophthalmology 110:956-961, 2003). Often diagnosed late due to a lack of early symptoms, this kind of melanoma is associated with a poor prognosis. Approximately 50 % of the patients develop distant metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…GSEA analysis showed that positive regulation of T cell mediated pathways and malignant hallmarks such as mTORC1 signaling, oxidative phosphorylation, interferon-a response and apoptosis signaling positively activate in C1 subgroup. In fact, T cells like active CD 4 + and CD 8 + cells have antitumor immunity and therapy functions [17]. As to C1 molecular subtype, lots of malignant hallmark of pathways were enriched.…”
Section: Discussionmentioning
confidence: 99%
“…GSEA analysis showed that positive regulation of T cell mediated pathways and malignant hallmarks such as mTORC1 signaling, oxidative phosphorylation, interferon-a response and apoptosis signaling positively activate in C1 subgroup. In fact, T cells like active CD 4 + and CD 8 + cells have antitumor immunity and therapy functions [17]. As to C1 molecular subtype, lots of malignant hallmark of pathways were enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high metastatic risk can be identified using validated prognostic tests such as chromosome 3 status [42], gene testing for class 1 (low metastatic risk) and class 2 (high metastatic risk) [43] or molecular stratification according to somatic copy number alterations and DNA methylation profiles [44]. There are innovative clinical trials in which high risk, monosomy 3, HLA-A2+ uveal melanoma patients are vaccinated with either melanoma antigen-derived peptides or melanoma antigen-encoding mRNA transfected-DC in the prophylactic setting [4548]. These immunotherapy trials are unique in that patients are vaccinated at early time points when there is no clinical evidence of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The eye is considered an immune-privileged organ which influences the immune response against uveal melanoma cells and provides escape mechanisms for uveal melanoma [95]. The following factors play an important role in the immune privilege of the eye: aqueous humor is rich in immunosuppressive proteins, such as transforming growth factor β (TGF-β), vasoactive intestinal peptide (VIP), α-melanocyte-stimulating hormone (α-MSH), and complement regulatory proteins (CRPs); the blood-eye barrier restricts inflammatory cell access to the eye; eye cells reduce major histocompatibility complex (MHC) class Ia expression to escape cytotoxic-mediated lyses; and ocular cells express programmed death ligand-1(PD-L1) which inhibits T-cell response.…”
Section: Systemic Immunotherapymentioning
confidence: 99%
“…To date, there are no treatments that target NK cells or macrophages. Regarding adaptive immune response, the mechanisms that interfere with immunity are the production of indoleamine 2,3-dioxygenase (IDO), overexpression of PD-L1, alteration of FasL expression, and resistance to perforin [16,95].…”
Section: Systemic Immunotherapymentioning
confidence: 99%